(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: According to the Agency for Healthcare Research and Quality, "A pressure ulcer is defined as a localized injury to the skin or underlying tissue, usually over a bony prominence, resulting from prolonged pressure, leading to ischemia, cell death, and tissue necrosis." Pressure ulcers represent a significant cost burden, impacting hospital stays and long-term care. Objective: To determine the percentage of nurses with proper knowledge, attitudes, and compliance in assessing and intervening in pressure ulcer risk based on the Braden scale and to identify related factors. Subjects and Research Methodology: A cross-sectional descriptive study conducted at Thu Duc City Hospital from April to September 2023 on nursing staff working in inpatient departments, with a final sample size of 158. Data were analyzed using SPSS version 22.0. Factors related to medication compliance were identified using T-tests, Fisher’s exact test, and ANOVA. Results: Nurses’ knowledge was generally good (mean score: 30.19 ± 2.19), attitude was moderately positive (mean: 3.62 ± 0.54), and compliance was fairly good with a rate of 62.7%. There was a statistically significant relationship between knowledge and nurses’ attitudes (p < 0.001). No direct correlation was found between knowledge, attitude, and compliance. However, a connection between knowledge and attitude was noted with certain components of compliance.